Short-Spindled Cell Haemangioblastoma with CD34 Expression: New Histopathological Variant or Just a Stochastic Cytological Singularity? - Miguel Fdo. Salazar; Paola Andrea Escalante Abril; María Verónica Velasco Vales; Celene Martínez Ruiz; Erick Gómez Apo; Laura G. Chávez Macías (Case Reports in Pathology)
Haemangioblastomas are neoplasms of uncertain histogenesis with cellular and reticular variants advocated in current lore. Herein we describe an intriguing cerebellar specimen with unusual traits including spindle cell morphology and CD34 positivity. A thirty-nine-year old man had an infratentorial tumour discovered incidentally and resected three times. In all the instances, histopathological diagnosis was haemangioblastoma; nonetheless, he had neither physical stigmata nor family history of von Hippel-Lindau disease. By histology, the lesion was composed of areas of conventional stromal cells admixed with territories populated by short-spindled cells packed in lobules, sometimes giving the appearance of gomitoli. Immunoperoxidase-coupled reactions confirmed the expression of inhibin A, neuron-specific enolase (NSE), PS100, and CD57 but also revealed focal immunolabeling for CD34, CD99, and FXIIIa. This case highlights the potential phenotypical diversity that can be found within these neoplasms. Rather than uncertain histogenesis, it may in fact reflect multiple lines of differentiation—histomimesis—prone to adopt unusual morpho- and immunophenotypes in a subset of haemangioblastomas.